Q. 165.0( 2 Votes )

# If *x*+1 is a factor if the polynomial 2*x*^{2}+*kx*, then *k* =

A. -2

B. -3

C. 4

D. 2

Answer :

Let, f (x) = 2x^{2} + kx

Since, x + 1 is divided by f (x) so,

f (-1)=0

2 (-1) + k (-1) = 0

k = 2

Rate this question :

Using factor theorem, factorize each of the following polynomial:

*x*^{3}-10*x*^{2}-53*x*-42

If *f*(*x*) =*x*^{4}-2*x*^{3}+3*x*^{2}-*ax*-*b* when divided by *x*-1, the remainder is 6, then find the value of *a* + *b*

Using factor theorem, factorize each of the following polynomial:

2*y*^{3}-*5y*^{2}-19*y*+42

Using factor theorem, factorize each of the following polynomial:

*x*^{3}-2*x*^{2}-*x*+2

Using factor theorem, factorize each of the following polynomial:

2*y*^{3}+*y*^{2}-2*y*-1

Using factor theorem, factorize each of the following polynomial:

*y*^{3}-2*y*^{2}-29*y*-42

If *x*+1 is a factor of *x*^{3}+*a*, then write the value of *a*.

If x^{2}-1 is a factor of *ax*^{4}+*bx*^{3}+*cx*^{2}+*dx*+*e*, then

If *x*+1 is a factor if the polynomial 2*x*^{2}+*kx*, then *k* =

If *x*+2 is a factor of x^{2}+*mx*+14, then *m* =